Optimal Design of Securities under Asymmetric Information - Nachman, David C.; Noe, Thomas H. (Review of Financial Studies, 1994)
A firm must decide what security to sell to raise external capital to finance a profitable investment opportunity. There is ex ante asymmetry of information regarding the probability distribution of cash flow generated by the investment. In this setting, we derive necessary and sufficient conditions for a security to be optimal (uniquely optimal), that is, for pooling at this security to be an (the unique) equilibrium outcome. Using these conditions we show that the debt contract is (uniquely) optimal if and only if cash flows are ordered by (strict) conditional stochastic dominance. Finally, we derive an equivalence relationship between optimal security designs and designs that minimize mispricing.